Risk management in a volatile market - Singapore Management University (Institutional Knowledge at Singapore Management University, 2012)
As stock markets around the world whipsaw in a manner that bewilders even the seasoned trader, an academic has suggested for financial institutions to look more closely at linking dynamic loss tail distributions to contagion modeling for effective risk management.